P-58 Hospice care for marginalised people – the safe harbour approach. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Carpenter, Jane
Abstract : Background: Access to palliative care nationally is inequitable (Sleeman, 2016), with recognition that marginalised people do not receive hospice care in the way that other groups do (CQC, 2016). Our hospice strategic aim is to reach unmet need and address inequality of access. Locally, groups identified to have unmet needs are: the homeless community, substance misusers, adults with enduring mental health issues, patients from minority ethnic groups, and transgender patients. Approach: The 'Safe Harbour' project was set up to address this unmet need. Those involved: Made themselves visible and approachable by attending homeless service drop-ins, addiction services, community network groups, beach cleans, food banks and health forums. Listened to our local community, service users, community groups and voluntary organisations, and carried out a detailed needs assessment. This demonstrated that we were prepared to talk openly about what we already do, to offer support to community members with unmet palliative and end of life care needs. Ensured that the hospice team were ready and competent to care for people with a wide spectrum of medical and psychosocial need. Worked with other key providers to ensure collaborative, effective support by those professionals best placed to care, including social care, mental health services, national and local charities. Case-management of the most complex marginalised palliative patients. Outcome: We have established a service to support the marginalised population in our local area. One of the measures of the success of this service has been an increase from one to ten people from the marginalised community, able to die away from hospital last year. Conclusion: Taking time to gain the confidence of people, who traditionally have not trusted those in authority, has meant that this service is now being used by the most marginalised of our population. The model could be used as a template for other hospices.